IGF expression in HPV-related and HPV-unrelated human cancer cells - DURZYŃSKA, JULIA (D.A. Spandidos, 2014)
The human Igf-1 gene not only produces insulin-like growth factor-I (IGF-I), but also different carboxy-terminal extensions, known as E peptides, through alternative splicing. We and others have shown that human Eb peptide (hEb) derived from Igf-1 has intrinsic biological activity and is localized to nuclei of transfected cells. Since hEb actions can complement the activity of IGF-I itself, the aim of the present study was to compare IGF-I isoforms at the endogenous protein and transcript level in cancer cell lines, including HeLa, U2OS, HepG2 and K562 cells. Quantitative real-time PCR (qRT-PCR) using Igf-1 isoform specific primers was performed to determine expression patterns, using β-actin as a reference gene. The overall relative Igf-1 transcript level was different across the cell lines, with ~80-fold higher expression in K562 (130.2±31.2) than in U2OS cells (1.7±1.1). The relative copy number of Igf-1b was the highest in HepG2 (69.9±28.6) and K562 cells (28.3±6.7), whereas the relative copy numbers of Igf-1a and Igf-1c were significantly higher in K562 cells compared to all other cell lines. Immunoblotting using total cell lysates, cytoplasmic and nuclear fractions were carried out to determine the level and distribution of IGF-I proteins. K562 cells exhibited the highest level of hEb in total cell lysates and nuclear fractions and no cell lines displayed hEb in the cytoplasmic fractions. In contrast, IGF-IA was the highest in HeLa cells and was enriched only in the cytoplasmic fraction. Since relatively low IGF-1A transcript level but relatively high pro-IGF-1A protein level is plausible, we hypothesized that these transcripts could be processed with higher efficiency and/or the protein product may be stabilized by viral HPV oncogenes in HeLa cells. We assert that while it is important to analyze Igf-1 transcript level, it may be more relevant to determine the IGF isoforms at the protein level.